PORE SIZE DIAMETER, SHRINKAGE AND SPECIFIC GRAVITY EVOLUTION DURING THE HEAT TREATMENT OF WOOD (Innovation in Woodworking Industry and Engineering design, 2026)
The heat treatment of wood by mild pyrolysis permit to produce a new material called torrefied or retified wood. Heat treated wood possesses new properties like improved decay resistance, higher dimensional stability, hydrophobic character, while strength properties are considerably reduced. The aim of this work was to study the anatomical structure evolution during heat treatment to explain the decreasing of the mechanical properties. The heat treatment has been carried out for a very large temperature range between 180 to 345°C under inert atmosphere on tow European wood species (pine and beech). The anatomical structure has been investigated by Scanning Electron Microscopy before and after heat treatment. On wood block for different treatment temperature mass, volume and shrinkage has been measured. From these results the apparent specific gravity was calculated and the porosity variation estimated. The results of the observations show that they are no evolution of the macroscopic anatomical structure, the vessels and tracheïds diameters remain constant. The volume evolution is probably caused by the diminution of the cellular wall thickness. By combining specific gravity evolution and the microscopic observation it's possible to conclude that the wood porosity increase on a scale lower than the micrometer (meso or nano porosity)